Modified abdominal wall suspension system in gasless laparoscopy: A clinical application - Li, Yin Feng; Adlan, Aizura Syafinaz; Gao, Li Li; Feng, Mei Ying; Yu, Hai Tin; Ru, Shi; Lin, Bao Liang (S.O.G. CANADA Inc., 2018)
Introduction: The gasless laparoscopic technique is easily operable, safe. and avoids complications of pneumoperitoneum. The suspension method from two celiac wall rods evolved to a single wall rod method, reducing one hanging rod on one side of the abdominal wall. This benefited the surgeon which reduced the inhibition of one less visible, space-consuming suspension rod, however remains a hindrance to the assistant's optimal movement and visual field. Objective: To explore the feasibility and application value of a modified abdominal wall suspension system in standard gasless laparoscopic myomectomy. Materials and Methods: Women agreeing to participate were randomised into two arms. The standard conventional gasless method versus the modified abdominal wall lifting method. Results: A total of 100 women were randomised into two groups; the improvised technique (group 1) and the conventional technique (group 2). Surgical operating time (72.3 ± 35.6 minutes [improved] and 82.7 ± 31.9 minutes [conventional]) p < 0.01), total blood loss (204.9 ± 167.3 ml [improved] and 266.7 ± 190.5 ml [conventional], p < 0.01)) and average time of a single-myoma-removal (improved vs. conventional) were significantly reduced in the improvised technique group, as opposed to the conventional technique group. No significant difference was found between the two groups with regards to postoperative intestinal function recovery period or the postoperative hospital stay duration. Conclusion: The modified abdominal wall suspension method increases the surgeon's operating space, making it more convenient and practical with significant rewarding postoperative surgical outcomes.